ELECTROCHEMICAL SYNTHESIS OF COMPLEX OF COPPER (II ) WITH TYPE LIGAND BENZOILTIOUREAS MONOSUBSTITUTED - Angulo-Cornejo, J. (1999)
In this study reported some progress in the synthesis of copper ( II ) with ligands monosubstituted benzoiltioureas type , by ico electroquím method. According to this objective we have apl I ied the following procedure has been synthesized ligand 1-phenyl -3 - benzoylthiourea ( H2L ) , which has been characterized by anal y elemental sis, and IR spectroscopy , 1H - NMR , 13C NMR and mass spectrometry . 1H NMR spectroscopy confirms the presence of a hydrogen bond between the proton type of CS- NH group and the oxygen of the CO group . Have synthesized two complexes of copper , the first complex of copper (I) corresponds to a stoichiometric ( 1: 1) [Cu ( I) - L ] n , which was prepared by direct reaction of an ethanolic solution of the ligand and copper acetate ( II ) in equimolar ratio , the second complex was synthesized by the electrochemical method , a Cu ( HL ) 2 stoichiometry . The complexes were characterized by IR spectroscopy , elemental analysis and by measurements of magnetic susceptibility